Intellectual capital and financial performance of Islamic banks - Ousama, Abdulrahman Anam; Abdul Hamid, Fatima (Inderscience Enterprises Ltd., 2015)
This paper measures the value added intellectual coefficient (VAIC™) for corporate efficiency performance of the Islamic banking sector in Malaysia. In addition, the paper examines the relationship between IC efficiency and financial performance. The paper used secondary data which was collected from the annual reports for the years 2008, 2009 and 2010. The paper found that the overall IC efficiency (i.e., VAIC) of this study's sample is higher than that of conventional banks' of prior studies. In addition, the paper found that human capital efficiency is higher than the structural capital and capital employed efficiencies. Furthermore, the paper found that IC efficiency influences the profitability of Islamic banks. The findings provide empirical evidence that the optimal utilisation of IC and resources leads to higher bank profitability. Therefore, these findings could be useful as Islamic banks that would like to further improve their financial performance could focus on improving their IC.